Farklı İnancı Tehdit Olarak Algılamanın Sonucu Engizisyon Terörü - Ahmet Hikmet Eroğlu (Dini Araştırmalar, 2015)
Terror; although today it gained a world wide dimension, is not a phenomenon peculiar only to the modern world. The past of terror relying on religion can be traced back to very old times. The most well-known terror depending on the interpretations of Christianity is the Inquisitorial terror. The Inquisitorial terror is the result of perceiving different views as threat The signs of the fact that the Western countries began to see the different views as threat have recently appeared. And this causes an anxiety that the inquisitonal mentality may arise from the dead once again. To know the reason causing the inquisitorial terror to appear will make contribution to understand the nature of terror depending on religion and to take measures against it